Use of an Anopheles Salivary Biomarker to Assess Malaria Transmission Risk Along the Thailand-Myanmar Border. (7th December 2016) - Ya-umphan, Phubeth; Cerqueira, Dominique; Parker, Daniel M.; Cottrell, Gilles; Poinsignon, Anne; Remoue, Franck; Brengues, Cecile; Chareonviriyaphap, Theeraphap; Nosten, Francois; Corbel, Vincent
Abstract: Background: The modalities of malaria transmission along the Thailand-Myanmar border are poorly understood. Here we address the relevance of using a specific Anopheles salivary biomarker to measure the risk among humans of exposure to Anopheles bites. Methods: Serologic surveys were conducted from May 2013 to December 2014 in 4 sentinel villages. More than 9400 blood specimens were collected in filter papers from all inhabitants at baseline and then every 3 months thereafter, for up to 18 months, for analysis by enzyme-linked immunosorbent assay. The relationship between the intensity of the human antibody response and entomological indicators of transmission (human biting rates and entomological inoculation rates [EIRs]) was studied using a multivariate 3-level mixed model analysis. Heat maps for human immunoglobulin G (IgG) responses for each village and survey time point were created using QGIS 2.4. Results: The levels of IgG response among participants varied significantly according to village, season, and age ( P <.001) and were positively associated with the abundance of total Anopheles species and primary malaria vectors and the EIR ( P <.001). Spatial clusters of high-IgG responders were identified across space and time within study villages. Conclusions: The gSG6-P1 biomarker has great potential to address the risk of transmission along the Thailand-Myanmar border and represents a promising tool to guide malaria interventions.